KOORDINASI PEMERINTAH KECAMATAN WELIMAN KABUPATEN MALAKA - Minggus Dominggus Seran; Wilfridus Taus; Nikolaus Uskono (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Timor, 2025)
This study examines coordination practices within the Weliman District Government in carrying out governmental functions. A descriptive qualitative approach was employed using observation, in-depth interviews, and documentation analysis. The findings show that internal coordination is conducted through routine weekly and monthly meetings and official circulars, generally aligned with annual plans and established agendas. However, coordination effectiveness is constrained by weak cross-unit communication that leads to miscommunication, as well as limited human resources in terms of both quantity and capacity. External coordination functions to convey government directions to the community, supporting mutual understanding and encouraging public cooperation in line with district objectives. Horizontal coordination is implemented through regular meetings, coordination forums, and cross-sector communication involving task division, information exchange, and joint decision-making. Nevertheless, limited commitment and responsiveness from some stakeholders, along with constraints in time, budget, and energy, hinder optimal outcomes. Vertical coordination plays a strategic role in ensuring effective governance and security at the sub-district level, yet its implementation remains suboptimal. Strengthening inter-agency collaboration, establishing consistent communication forums, improving data and information support, and fostering shared commitment among leaders and law enforcement agencies are essential to enhance coordination and public service delivery.